Correlation functions in super liouville theory - Abdalla, E.; Abdalla, M. C B [UNESP]; Dalmazi, D. [UNESP]; Harada, Koji (American Physical Society (APS), 1992)
We calculate three- and four-point functions in super Liouville theory coupled to a super Coulomb gas on world sheets with spherical topology. We first integrate over the zero mode and assume that a parameter takes an integer value. We find the amplitudes, give plausibility arguments in favor of the result, and formally continue the parameter to an arbitrary real number. Remarkably the result is completely parallel to the bosonic case.